2024
DOI: 10.1186/s12887-024-04606-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical punishment and effective verbal communication in children aged 9–36 months, according to sex: secondary analysis of a national survey

Vanessa Chire Illachura,
Maria Inés Montesinos-Malpartida,
Luciana Bellido-Boza
et al.

Abstract: Background A substantial number of children in the world are regularly subjected to physical punishment by their parents as a method of upbringing. Evidence suggests that it has negative effects on the development of brain function. However, evidence regarding its association with verbal communication is limited and heterogeneous. It is also unknown whether the effects are the same in both boys and girls; especially in the contexts of developing countries, where the highest rates of physical pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Numerous international studies have consistently shown that physical punishment negatively impacts child development, irrespective of its severity [25]. Key adverse outcomes identified include diminished moral internalization, increased antisocial and aggressive behaviors, both externalizing and internalizing behavior problems, lowered selfesteem, mental health issues, strained parent-child relationships, impaired cognitive and socio-emotional development, detrimental effects on brain development, and long-term consequences in adulthood such as continued antisocial behavior, mental health problems, and the perpetuation of physical punishment across generations [6,24,[26][27][28][29][30][31][32][33][34][35]. Notably, no research has established any positive effects of physical punishment [26], and a broad spectrum of literature further confirms its ineffectiveness as a disciplinary measure [28,[36][37][38].…”
Section: Physical Punishmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous international studies have consistently shown that physical punishment negatively impacts child development, irrespective of its severity [25]. Key adverse outcomes identified include diminished moral internalization, increased antisocial and aggressive behaviors, both externalizing and internalizing behavior problems, lowered selfesteem, mental health issues, strained parent-child relationships, impaired cognitive and socio-emotional development, detrimental effects on brain development, and long-term consequences in adulthood such as continued antisocial behavior, mental health problems, and the perpetuation of physical punishment across generations [6,24,[26][27][28][29][30][31][32][33][34][35]. Notably, no research has established any positive effects of physical punishment [26], and a broad spectrum of literature further confirms its ineffectiveness as a disciplinary measure [28,[36][37][38].…”
Section: Physical Punishmentmentioning
confidence: 99%
“…Physical punishment is a negative parental practice that is commonly used in early childhood [6][7][8]. Colombia is a country with a high prevalence of this negative parental practice [10,11].…”
Section: Practical Implications Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation